Design and analysis of integrated thermal protection system based on lightweight C/SiC pyramidal lattice core sandwich panel. (5th December 2016) - Wei, Kai; Cheng, Xiangmeng; Mo, Fuhao; Wen, Weibin; Fang, Daining
Abstract: Thermal protection system (TPS) plays the key role to successful development of hypersonic vehicles. Here, a novel structurally and thermally integrated thermal protection system (ITPS) based on the lightweight C/SiC pyramidal core lattice sandwich panel is proposed. This ITPS integrates advantages of low areal density and high temperature resistance up to 1600 °C. Heat transfer characteristics and compressive responses of the C/SiC sandwich panel are established in advance. The results demonstrate that filling alumina fibers in the pore significantly reduce the effective thermal conductivity from 2.45–4.83 W/m °C to no more than 0.7 W/m °C. The critical relative density is determinated for the failure models under aerodynamic pressure load. Meanwhile, an analysis procedure of the ITPS is exclusively established under typical aerodynamic heat flux and pressure load. With fulfillment of both temperature and mechanical constraints, minimum areal density is obtained. Compared with current metal corrugated core ITPS, the ITPS proposed here significantly raises the temperature limitation up to 1600 °C and reduces the areal density up to 35%, and is very promising for potential application in hypersonic vehicles. Graphical abstract: Highlights: Lightweight characteristic is realized as the relative density is only 8.58%. Filling alumina fibers reduce the effective thermal conductivity to about 0.7 W/m °C. Critical relative density is identified to ensure the core rod fracture failure. The proposed integrated thermal protection system reduces 35% of the areal density.